How ready are students to use ChatGPT? A study on instrument validity and reliability - Mohd Noh, Muhammad Naim; Mustafa, A’dillah; Baharuddin, Kasmarini (Faculty of Information Management, 2025)
This study reports the construct validity and reliability of an instrument designed to measure students’ behavioural intention to use ChatGPT. The instrument is developed based on the Unified Theory of Acceptance and Use of Technology (UTAUT) model. Data were collected from 65 undergraduate students of the Faculty of Information Management at UiTM Puncak Perdana using proportionate stratified sampling. Analyses conducted with SPSS and Smart PLS confirmed that the instrument demonstrated acceptable construct validity and moderate reliability. Internal consistency values included Cronbach’s alpha (0.810–0.929), composite reliability (0.70–0.90), and average variance extracted above 0.50. Model accuracy and relevance (R² and Q²) were within acceptable and moderate ranges, with no collinearity issues detected. Content validity was further established using CVI, S-CVI, and S-CVI/Ave, which exceeded 0.80, indicating strong agreement. Overall, the instrument achieved robust validity and reliability, offering a useful inventory for future research on ChatGPT adoption in education.